Consumers’ Assemblages of Fear and Safety with Firearms: Obstacles to Addressing Gun Violence in an Armed America - Barnhart,Michelle; Huff,Aimee; McAlexander,Jim; McAlexander,Brandon (Consumer Culture Theory Conference 2017, 2017)
Keywords: Marketing

Consumers' Assemblages of Fear and Safety with Firearms: Obstacles to Addressing Gun Violence in an Armed America - Huff,Aimee; Barnhart,Michelle; McAlexander,Brandon; McAlexander,Jim (Association for Consumer Research, 2017)
Keywords: Marketing

Consumers’ Assemblages of Fear and Safety with Firearms: Obstacles to Addressing Gun Violence in an Armed America - Barnhart,Michelle; Huff,Aimee; McAlexander,Jim; McAlexander,Brandon (Association for Consumer Research Conference 2017, 2017)
Keywords: Marketing

Consuming and Consumption in Third Space Communites: Constructing Sanctuary - McAlexander,Jim (ACR North American Conference, 2014)
Keywords: Marketing

Communitas Interruptus - McAlexander,Jim (European Advances in Consumer Research, 2010)
Keywords: Marketing

Contextual Influences: Building Brand Community in Large and Small Colleges - McAlexander,Jim; Koenig,Hal (Journal of Marketing for Higher Education, 2010)
This research extends recent efforts that have introduced and empirically tested a conceptual model of brand community in the context of higher education. This emerging literature has indicated that brand community provides a framework that can inform and guide marketing investments in ways that lead to affinity and stronger loyalty to the brand and institution. This paper presents the results of a national survey that examines the potential impact that institutional size may have on the relationships of an alumni brand community. This paper also explores the implications of the size of the educational institution on relevant and desired marketing outcomes that include the willingness to recommend the university to friends and family and a desire to purchase licensed apparel
Keywords: Marketing

Claiming the Throttle: Multiple Feminities in a Hyper-Masculine Subculture - Martin,Diane; Schouten,John; McAlexander,Jim (Consumption, Markets and Culture, 2006)
This feminist re-examination of an ethnography of Harley-Davidson motorcycle owners uncovers a world of motivations, behaviors, and experiences undiscovered in the original work. The structure and ethos of subculture are understood differently when examined through the lens of feminist theory. Through the voices of women riders in a hyper-masculine consumption context we discover perspectives that cannot easily be explained by extant theory of gender and consumer behavior. We find women engaging, resisting, and co]opting hyper-masculinity as part of identity projects wherein they expand and redefine their own personal femininities. This study reveals invisible assumptions limiting the original ethnography and thus reiterates the problems of hegemonic masculinity in the social science project.
Keywords: Marketing

A Cross-Cultural Exploration of Subcultures of Consumption - McAlexander,Jim; Fushimi,Katsu; Schouten,John (Research in Consumer Behavior, 2000)
Keywords: Marketing

Close to the Customer: Gonzo Research in an Age of Quality - McAlexander,Jim (Presentation to the Portland Rotary Club, 1995)
Keywords: Marketing

Consumer Behavior and Divorce - McAlexander,Jim; Schouten ,John; Roberts ,Scott D. (Research in Consumer Behavior, 1993)
Keywords: Marketing